A szimmetria jelenléte Silviu Purcărete előadásaiban - Böjthe Pál (Symbolon)
The Presence of Symmetry in Silviu Purcărete’s Performances The Greek word symmetry means correct proportion. The basis for this study is the interesting fact according to which symmetry has been known to be the father of boredom in the theatre at least since Meiningenism. To describe a work of art as symmetrical is to say that the bisector axis divides the whole into two exactly corresponding parts. This articulation expresses immobility and constancy, and evokes a sense of these in the viewer, or in the listener in the case of a poem, theatre or music performance. Therefore, the more or less regular use of symmetry today seems a kind of reminiscence of a hundred years ago. In contrast, Silviu Purcărete – whom Lehmann classifies as a post-dramatic director, and who, according to other opinions, can be considered a fully 21st-century director – is a keen user of symmetry in his performances. We will first briefly discuss the concept of symmetry. This will be followed by examples of symmetry from three theatre performances by Silviu Purcărete. Finally, some reflections are presented on the use of symmetry in Silviu Purcărete’s case.